Factors affecting thermal conductivities of the polymers and polymer composites: A review - Guo, Yongqiang; Ruan, Kunpeng; Shi, Xuetao; Yang, Xutong; Gu, Junwei (Composites science and technology, 2020)
It is of considerable scientific and technological importance to enhance the thermal conductivity coefficient (λ) values of the polymers and polymer composites. Limited understanding of heat transfer in polymers and polymer composites imposes restrictions on the designing and fabricating better thermally conductive polymers and polymer composites. This review attempts to help understand the thermal conduction mechanisms by analyzing the effects of different components in polymers and polymer composites on heat transfer. Factors of micro- and macro-characteristics, such as chain structures, interfaces, functionalization and processing techniques, etc., are all illustrated to elucidate their impacts on the thermal conductivities. In general, chain structures of polymers, intrinsic λ values of thermally conductive fillers and interfacial thermal resistances are the main and internal factors to determine the λ values of polymers and polymer composites. Meantime, processing and environmental factors are only auxiliary factors to improve the thermal conductivities. We expect this review will give some guidance to the future studies in thermally conductive polymers and polymer composites.